2013
DOI: 10.1002/mds.25634
|View full text |Cite
|
Sign up to set email alerts
|

Persistent figure‐eight and side‐to‐side head shaking is a marker for rhombencephalosynapsis

Abstract: Background Head-shaking stereotypies have been described in patients with neurological impairment. We noted an unusual preponderance of head shaking in patients with rhombencephalosynapsis (RES). We sought to delineate the movements further and determine whether oculomotor and vestibular testing could reveal their cause. Methods Information was collected from direct observation, video review and parental questionnaire from 59 patients with RES. Oculomotor and vestibular testing was performed in 4 children. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 21 publications
0
14
1
Order By: Relevance
“…The cerebellum sends excitatory projections directly to the thalamus, amygdala, ventral tegmental area, and dorsal raphe nuclei and indirectly to the basal ganglia through the thalamus and amygdala . Furthermore, there are multiple reports, including this case, of stereotypies associated with cerebellar malformation . Cerebellar strokes in adults have also been reported to cause stereotypic movements, including rubbing thumbs against the index finger and unilateral movements of the hand and extremity .…”
Section: Case Reportmentioning
confidence: 83%
See 2 more Smart Citations
“…The cerebellum sends excitatory projections directly to the thalamus, amygdala, ventral tegmental area, and dorsal raphe nuclei and indirectly to the basal ganglia through the thalamus and amygdala . Furthermore, there are multiple reports, including this case, of stereotypies associated with cerebellar malformation . Cerebellar strokes in adults have also been reported to cause stereotypic movements, including rubbing thumbs against the index finger and unilateral movements of the hand and extremity .…”
Section: Case Reportmentioning
confidence: 83%
“…Figure of eight movements observed in RES are generally considered a stereotypy. Some investigators, however, hypothesized that they were secondary to disruption of central vestibular processing, based on the presence of subtle eye movement abnormalities such as hypometric saccades and deficits in smooth pursuit . Nevertheless, these same researchers acknowledged that their subjects frequently had complex motor stereotypies involving the limbs as well as the presence of common comorbidities observed in children with stereotypies, for example, tics, attention deficit hyperactivity disorder ADHD, and obsessive‐compulsive disorder OCD—symptoms not explainable solely as a deficit in vestibular processing.…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…Some research have demonstrated a deficit in the central vestibular processing, thus, this stereotype is an involuntary movement to obtain additional sensorial information. The pattern of movement, would activate semicircular canals and afferent nerve fibers, which increases the inputs in an abnormal vestibular system 23 . The cerebral magnetic resonance, a study of choice in GLHS besides showing rhombencephalosynapsis ( Figure 1) and triventricular hydrocephalus, it can highlight corpus callosum hypoplasia, absence or septum pellucidum lipoma and septo-optic dysplasia with hypothalamic-pituitary dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Rhombencephalosynapsis is defined by agenesis of the vermis and fusion of the cerebellar hemispheres across the midline . About 85% of patients with rhombencephalosynapsis have head‐shaking movements characterized by a rhythmic, repetitive, figure‐of‐eight or occasionally side‐to‐side swinging motion that may be intermittent or almost constant . As with head titubation in Joubert syndrome, the movements occur most frequently during times of fatigue or excitement, but their frequency is lower and amplitude larger compared to the head titubation in Joubert syndrome .…”
Section: Discussionmentioning
confidence: 99%